Liver function in children with human immunodeficiency virus infection before and after 6 months of highly active antiretroviral therapy - Eva Jacomina Jemima Sapulete; I Gusti Ngurah Sanjaya Putra; Ketut Dewi Kumara Wati; Hendra Santoso; I Putu Gede Karyana; Komang Ayu Witarini; Ni Nyoman Metriani Nesa (Paediatrica Indonesiana, 2018)
Background Highly active antiretroviral therapy (HAART) has resulted in dramatic decreases in morbidity and improved survival rate in human immunodeficiency virus (HIV)-infected patients. Although the risk of morbidity has decreased, it has been replaced by other long-term complications, such as hepatotoxicity. Hepatotoxicity is often reflected in biochemical abnormalities of liver function, such as elevated levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and aspartate aminotransferase-to-platelet ratio index (APRI). Objective To compare liver function spectrum (AST, ALT, and APRI) in HIV-infected children before and after at least 6 months of HAART. Methods This observational study (before and after) was conducted in pediatric patients with HIV infection who received HAART for at least 6 months at Sanglah Hospital, Denpasar. Data were collected from medical records. Results Forty-nine patients were observed in this study. The mean AST, ALT, and APRI levels before HAART were higher than after at least 6 months of HAART. Anti-tuberculosis treatment and fluconazole therapy were not confounding factors for AST, ALT, and APRI. Conclusion Liver function spectrum enzyme levels of AST, ALT, and APRI are improved after at least 6 months of HAART.